PEMETAAN BENCANA SOSIAL DAN BENCANA ALAM DI KOTA SAMARINDA - Maskan Dan Florentinus Sudiran (Prodi Ilmu Administrasi Negara, 2017)
Research mapping of disaster-prone areas / social conflicts in Samarinda City, East Kalimantan Province, is intended to mapping the identification of vulnerable areas of social conflict, finding out the source of the problem (root) causes of social conflict as well as solutions and recommendations for conflict prevention and cessation of various approaches, local.Based on the description of the data presentation and the summary of the research results (problems and potential threats of conflict) at the research sites are not very different, there are some similarities of current and future conflict identification, in sequence the potential threat of conflict is more dominant in aspects of Poleksosbud, Boundaries and aspects of SARA.Based on the description of potential disaster / conflict potentials mentioned above, alternative solutions and recommendations for preventing and stopping social conflicts in East Kalimantan include the need for synergy between the roles of government, TNI - POLRI, private sector and key figures, peace advocacy, creating and optimizing social communication based Local wisdom, identification of potential threats to social conflicts, and enforcing strict law enforcement against perpetrators of destruction / Korlap / in charge of social conflicts.